A Geographical Information System based framework to identify optimal location and size of biomass energy plants using single or multiple biomass types. (1st October 2020) - Jayarathna, Lasinidu; Kent, Geoff; O'Hara, Ian; Hobson, Philip
Highlights: Development of an integrated GIS tool for optimal locating of biomass energy plants. Calculation of optimum locations, sizes and corresponding biomass delivery cost. Evaluation of sugarcane and forest waste for bioelectricity generation. The delivery cost of sugarcane waste alone ranged from AUD 142 to 198 per dry tonne. By combining two biomass sources, plant sizes could increase between 3% and 31% Abstract: The highly dispersed nature of biomass sources and limited tools with which to exploit geographically explicit data to minimise delivery costs are major barriers to the initiation of biomass energy projects. This paper presents a geographical information system based approach in combining suitability analysis, spatial biomass assessment and optimality analysis to locate plants for bioelectricity generation with sustainable availability of single or multiple biomass. First, fuzzy multi-criteria analysis was employed to identify the suitability of plants' locations, using local economic, environmental, and social sustainability criteria. As well, the availability of multiple types of biomass was assessed. Biomass availability information and land use data were combined to generate high-resolution spatial biomass information with user-defined resolution. Next, a location-allocation model was used to identify optimal locations for biomass energy plants by considering both road networks and spatially distributed biomass availability. Additionally, different scenarios were analysed to optimise plant sizes, biomass delivery costs and total number of plants for the region under both single biomass and multi-biomass approaches. The developed model was demonstrated for a Queensland case study using sugarcane waste alone and combined sugarcane waste and forest waste. Results using sugarcane waste in Queensland identified optimally located plants with sizes from 57 MW to 185 MW and average transportation distances of 27 km to 64 km. By combining sugarcane waste with forest waste, the plant sizes increased, depending on spatial biomass availability. This methodology can be extended to evaluate optimum configuration and optimum combination of different biomass types at a plant level.